THE PECULIARITIES OF FORMING NATIONAL PATRIOTISM IN THE CONTEXT OF GLOBALIZATION - Murodulayev Temur Abdulla o‘g‘li (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The process of globalization is having a profound impact on all aspects of the global community. This process manifests itself in social, economic, and cultural spheres, raising concerns about preserving national identity and values. From this perspective, instilling the idea of national patriotism among young people becomes a crucial factor in ensuring the stability and development of a country in the era of globalization.